Automatic Coffee Roasting System With Arduino Uno Based Temperature Control - Arsy Febrina Dewi; Asnawi Yoga; Rusli Rusli (Universitas Islam Raden Rahmat, Malang, 2026)
Coffee is a popular and widely enjoyed beverage. To produce delicious coffee, quality coffee beans are essential. Quality coffee beans are crucial to achieve the desired taste and aroma. One important process is the coffee roasting process. Manual roasting involves heating coffee beans to a certain roasting level. This process is highly dependent on human perception. To address this issue, the study aims to create an automatic coffee roasting system based on temperature control for three roasting levels: light roast, medium roast, and dark roast. This system is designed with temperature control for the light roast category ranging from 196-197°C with a duration of 11 minutes, medium roast ranging from 210-211°C with a duration of 13 minutes, and dark roast ranging from 230-231°C with a duration of 15 minutes. The system design uses heating elements, servo motors, temperature sensors, and an Arduino Uno microcontroller. Tests were conducted on coffee beans with a capacity of 0.5 kg to 2 kg. Based on the test results, there was a decrease in water content in coffee beans for each roasting category and the system will display the conditions of water content, time, and roasting temperature tested before and after roasting.